Long-Term Simulation of Daily Streamflow Using Radar Rainfall and the SWAT Model: A Case Study of the Gamcheon Basin of the Nakdong River, Korea - Huiseong Noh; Jongso Lee; Narae Kang; Dongryul Lee; Hung Soo Kim; Soojun Kim (Advances in Meteorology)
In recent years, with the increasing need for improving the accuracy of hydrometeorological data, interests in rain-radar are also increasing. Accordingly, with high spatiotemporal resolution of rain-radar rainfall data and increasing accumulated data, the application scope of rain-radar rainfall data into hydrological fields is expanding. To evaluate the hydrological applicability of rain-radar rainfall data depending on the characteristics of hydrological model, this study applied Rgauge and Rradar to a SWAT model in the Gamcheon stream basin of the Nakdong River and analyzed the effect of rainfall data on daily streamflow simulation. The daily rainfall data for Rgauge, RZ, and RKDP were utilized as input data for the SWAT model. As a result of the daily runoff simulation for analysis periods using RZ(P) and RKDP(P), the simulation which utilized Rgauge reflected the rainfall-runoff characteristics better than the simulations which applied RZ(P) or RKDP(P). However, in the rainy or wet season, the simulations which utilized RZ(P) or RKDP(P) were similar to or better than the simulation that applied Rgauge. This study reveals that analysis results and degree of accuracy depend significantly on rainfall characteristics (rainy season and dry season) and QPE algorithms when conducting a runoff simulation with radar.